Gastroschisis in Uganda: Opportunities for improved survival - Wesonga, Anne S.; Fitzgerald, Tamara N.; Kabuye, Ronald; Kirunda, Samuel; Langer, Monica; Kakembo, Nasser; Ozgediz, Doruk; Sekabira, John (Journal of pediatric surgery, 2016)
Neonatal mortality from gastroschisis in sub-Saharan Africa is high, while in high-income countries, mortality is less than 5%. The purpose of this study was to describe the maternal and neonatal characteristics of gastroschisis in Uganda, estimate the mortality and elucidate opportunities for intervention. An ethics-approved, prospective cohort study was conducted over a one-year period. All babies presenting with gastroschisis in Mulago Hospital in Kampala, Uganda were enrolled and followed up to 30days. Univariate and descriptive statistical analyses were performed on demographic, maternal, perinatal, and clinical outcome data. 42 babies with gastroschisis presented during the study period. Mortality was 98% (n=41). Maternal characteristics demonstrate a mean maternal age of 21.8 (±3.9) years, 40% (n=15) were primiparous, and fewer than 10% (n=4) of mothers reported a history of alcohol use, and all denied cigarette smoking and NSAID use. Despite 93% (n=39) of mothers receiving prenatal care and 24% (n=10) a prenatal ultrasound, correct prenatal diagnosis was 2% (n=1). Perinatal data show that 81% of deliveries occurred in a health facility. The majority of babies (58%) arrived at Mulago Hospital within 12h of birth, however 52% were breastfeeding, 53% did not have intravenous access and only 19% had adequate bowel protection in place. Four patients (9%) arrived with gangrenous bowel. One patient, the only survivor, had primary closure. Average time to death was 4.8days [range<1 to 14days]. The mortality of gastroschisis in Uganda is alarmingly high. Improving prenatal diagnosis and postnatal care of babies in a tertiary center may improve outcome.
Keywords: Neonatal surgery; Global health; Gastroschisis